Accentuation of general anaesthetic activity of ketamine by glutamate NMDA (N-methyl D-aspartate) receptor antagonist - Umamageswari, M. S.; ., Vasanthan; Kumar, Nikitha S. (International Journal of Basic & Clinical Pharmacology, 2018)
Background: The aim of the present study was to evaluate the potentiation of general anaesthetic activity of ketamine by NMDA receptor antagonist ‘amantadine’ in wistar albino rats. Methods: The wistar albino rats of either sex were divided into three groups of five animals in each group. Group I received ketamine 80mg/kg, group II received ketamine 40mg/kg along with amantadine 40mg/kg and group III received ketamine 80mg/kg along with amantadine 40mg/kg to evaluate the potentiation of general anaesthetic effect of ketamine. The sleep latency time and the total sleeping time were measured in all the three groups. Results: The sleep latency time of group III is significantly decreased (p <0.035) and as equal to that of group II when compared to group I. The sleeping time of group III is significantly increased (p <0.001) when compared to group I. Conclusions: Amantadine - the NMDA receptor antagonist potentiates the general anaesthetic activity of ketamine.